SOSIALISASI METODE PENYUBURAN TANAH UNTUK PENGENDALIAN KEKERINGAN DAN EROSI DI DESA MOLANIHU KECAMATAN BONGOMEME: SOSIALISASI METODE PENYUBURAN TANAH UNTUK PENGENDALIAN KEKERINGAN DAN EROSI DI DESA MOLANIHU KECAMATAN BONGOMEME - Sri Rahayu Ayuba; Dewi Sartika T Zees; Nursetiawati Nursetiawati (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
Drought and erosion are reducing soil fertility, which is a serious problem for the residents of Molanihu Village in Bongomeme District in Gorontalo Regency. The main source of income for the local population is agriculture, hence this has an effect on the local economy. To encourage farmers to actively participate in community service projects, a natural and environmentally safe method of enriching soil was provided. Participatory qualitative description was the method utilized in this exercise, which aims to collect detailed information about a problem. The primary participants in the program were thirty farmers. They learned about hydrosowing, planting legumes, conserving soil with plants, and using organic fertilizers. Farmers started to understand the idea of employing natural soil conditioning techniques and the potential for increased yields in a scenario of growing crop production. After applying organic fertilizers, soil fertility and agricultural productivity increased along with improvements in soil structure, water retention, and erosion rate. When applied as supplements to economic and agricultural outputs, these improvements proved advantageous. However, significant difficulties were caused by a lack of access to raw materials and fundamental resources for more efficient training. This program demonstrated how actively supporting farmers via education and training promotes environmentally responsible land management. Using organic fertilizers not only improves farmers' skills but also helps reduce pollution and prevent environmental disasters like erosion and drought.